FACTORS AFFECTING THE SUCCESSFUL TREATMENT OF LUNG TB IN THE HEALTH CENTER AREA HUTABALANG BADIRI DISTRICT IN 2022 - Muhammad Akhyar Nuary; Reni Aprinawaty Sirait (JURNAL KESMAS DAN GIZI (JKG), 2022)
Tuberculosis is a health problem that is the leading cause of death from infection worldwide, especially in developing countries. TB is an infectious disease caused by Mycobacterium tuberculosis. The World Health Organization (WHO) estimates that 1.3 million people will die from tuberculosis in 2016, and an additional 10.4 million will develop tuberculosis worldwide. This research aims to analyze the success of pulmonary TB treatment at the Hutabalang Health Center, Badiri District, which includes: age, education, income, knowledge, attitude and control of drug consumption with the success of pulmonary TB treatment at the Hutabalang Health Center, Badiri District. Quantitative research and survey methods with a Cross Sectional Study approach were chosen in this research. The results obtained are that there is a relationship between age, attitude and supervision of taking medication on the success of pulmonary TB treatment at the Hutabalang Health Center, Badiri District in 2022 with each p value of 0.003, 0.002 and 0.002.